PENGGUNAAN SMARTPHONE TERHADAP PERKEMBANGAN SOSIAL ANAK USIA 5-6 TAHUN - Najihatulkamilah; Herman Syafri; Qonita (LPPM Universitas Cipta Mandiri, 2025)
Technological development is undergoing an endless process of changes from time to time. There are technological tools that help ease and streamline human work, one of which is smartphones. This has become widespread among the public, adults and even young children can use smartphones. This fact is very worrying for young children, because some parents use smartphones as a soother when their children cry. In early childhood, children experience development in the stage of exploring and interacting with the environment. It is not uncommon for young children to play and satisfy their curiosity via smartphones, because for children smartphones are an interesting thing. Children's social development is related to how children are able to be confident, have honesty, and have a sense of empathy. So it is necessary for parents to accompany their children's social development, so that children develop as expected.